Perceptions of Brazilian university students on the impact of the COVID-19 pandemic on academic routine (Research, Society and Development, 2022)
The COVID-19 pandemic and disease containment measures impacted society around the world. The economy and education suffered a lot with the necessary adjustments to a new model. These adjustments affected students from Higher Education Institutions (HEIs) both public and private. This study investigated how exposure to the disease and changes in academic routine impacted HEI students. 401 students participated who answered an online form consisting of a sociodemographic questionnaire, exposure to COVID-19 and perception of economic and academic impact. It was found that 23.94% of students were unemployed and 8.48% of them suffered a reduction in the workload. In the academic aspect, 57.97% of students from private HEIs said they were satisfied with the measures adopted by the institutions, while 44.64% of students from public HEIs mentioned being dissatisfied with the measures adopted. In addition, the study showed that concern about the disease and its financial and academic impact affected the physical and emotional health of students, interfering with their right to a quality education. The data from the present study show the need for new efforts to guarantee qualified academic and professional training and the construction of a new society.